2022
DOI: 10.29121/ijoest.v5.i6.2021.257
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Nuclear Fusion Requirements in Bubbles During Ultra-High-Pressure, Ultra-High-Temperature Cavitation Promoted by Magnetic Field

Abstract: In the present work, a strong magnetic field was applied near the outlet of the water jet nozzle to promote the generation of multifunction cavitation bubbles. Because these bubbles contained charged species, the bubbles experienced a Lorentz force due to the magnetic field and collided with greater force. As such, the internal bubble pressure exceeded the threshold value required for fusion to occur. The expansion of these charged bubbles in response to ultrasonic irradiation affected adjacent charged bubbles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, if the bubble is in rapid motion, the Blake threshold increases. During MFC in the presence of a magnetic field, the charged bubbles will collide while driven by the Lorentz force and the number of high-temperature, high-pressure bubbles will increase Yoshimura et al (2021e), Yoshimura et al (2022). In the present study, the structure of the water tank Yoshimura et al (2021d), Yoshimura et al (2022) used in the reduced-size MFC apparatus was improved to make observations of the process easier.…”
Section: Experimental 21 Film Peeling Test For Viscoelasticity Evalua...mentioning
confidence: 87%
See 2 more Smart Citations
“…However, if the bubble is in rapid motion, the Blake threshold increases. During MFC in the presence of a magnetic field, the charged bubbles will collide while driven by the Lorentz force and the number of high-temperature, high-pressure bubbles will increase Yoshimura et al (2021e), Yoshimura et al (2022). In the present study, the structure of the water tank Yoshimura et al (2021d), Yoshimura et al (2022) used in the reduced-size MFC apparatus was improved to make observations of the process easier.…”
Section: Experimental 21 Film Peeling Test For Viscoelasticity Evalua...mentioning
confidence: 87%
“…The bubble size was determined to be 10 μm or less but the bubble temperature was increased to the same value as was obtained using the larger equipment Yoshimura et al (2021d). Previous work also established that the application of a magnetic field to this reduced-size MFC equipment using neodymium magnets activated the charged MFC bubbles while increasing the number of bubbles Yoshimura et al (2021e), Yoshimura et al (2022) The present study employed MFC in conjunction with a magnetic field (M-MFC) and investigated the effects of various parameters (specifically, the nozzle-resin distance and the presence of magnets) while processing samples of the thermoplastic resin polyamide 11 using a small-scale MFC apparatus Yoshimura et al (2022). Both these parameters were optimized and, using these optimized conditions, the ability of high-temperature and high-pressure M-MFC processing to reduce the surface viscoelasticity of the polyamide 11 was evaluated.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The authors also previously developed an energy-intensive MFC (EI-MFC) technology Yoshimura et al (2021a) that concentrates the ultrasonic irradiation generated in the vicinity of WJC bubbles, together with an MEI-MFC apparatus that applies a magnetic field to the EI-MFC process Yoshimura et al (2021a). A new metal processing technique referred to as laser-assisted EI-MFC (LMEI-MFC) was also demonstrated in prior studies Yoshimura et al (2021b), Yoshimura et al (2022b). This system combines an MFC system with irradiation by laser light in conjunction with the application of a strong magnetic field to promote multiphoton ionization within bubbles Yoshimura (2023a), Yoshimura et al (2023b).…”
Section: Introductionmentioning
confidence: 99%
“…Our own group has examined the feasibility of bubble nuclear fusion on an experimental and theoretical basis by superimposing Cavitation Fusion by Energy-Intensive Multifunction Cavitation in a Strong Magnetic Field with Laser Light Excitation International Journal of Engineering Science Technologies 51 magnetic field energy on a water jet Yoshimura et al (2022a), Yoshimura et al (2022b). This previous research demonstrated the generation of ultra-hightemperature, ultra-high-pressure cavitation producing the required fusion temperature of 1.0 × 10 8 K Yoshimura et al (2021a), Yoshimura et al (2018a), Yoshimura et al (2018b), Yoshimura (2020. The author's group has also developed a laser assisted magnetic field energy intensive multifunction cavitation (LMEI-MFC) apparatus intended for surface modification of various materials Yoshimura et al (2023).…”
Section: Introductionmentioning
confidence: 99%